PENGARUH VARIASI PRODUK DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN DENGAN KEPUASAN KONSUMEN SEBAGAI VARIABEL INTERVENING DI ANITA CAKE SITUBONDO - Wahida, Shinta Nur; Arief, Mohammad Yahya; Syahputra, Hendra (Fakultas Ekonomi dan Bisnis, 2023)
Marketing is one of the important factors in the company. It is also called the heart of company's life. The purpose of this study was to determine the effect of product variety and product quality on purchasing decisions and consumer satisfaction at Anita Cake in Situbondo. The population in this study were all consumers who ordered cake from Anita. The sampling method used simple random sampling with a total sample 93. Data analysis and hypothesis testing in this study used Partial Least Square – Structural Equation Modeling (PLS-SEM). The results of direct effect hypothesis testing used Smart PLS3.0 application showed that product variation has a significant effect on consumer satisfaction, product quality has no significant effect on consumer satisfaction, product variety and product quality have a significant effect on purchasing decisions, consumer satisfaction has a significant effect on purchasing decisions, product variety and product quality has a significant effect on purchasing decisions through consumer satisfaction.